(untitled) (Research, Society and Development, 2025)
Food labeling plays a vital role in food safety by providing information that ensures consumer protection and compliance with current legislation. However, family-run agro-industries face significant challenges in meeting legal requirements due to limited technical expertise and resources. This study aimed to evaluate the compliance of food product labels from agro-industries in the central region of Rio Grande do Sul with RDC 727/2022 and other Brazilian regulations. Between July and December 2024, products from six categories dairy, cereals, meats, sugar, beverages, and alcoholic beverages were analyzed. The evaluation was based on a 57-item checklist divided into 12 sections, addressing aspects such as ingredient lists, allergen warnings, and front-of-pack nutritional labeling. The results revealed differences in compliance levels among the groups, with alcoholic beverages showing the highest compliance (85.8%) and non-alcoholic beverages the lowest (68.5%). The most non-compliant items included origin identification, allergen warnings, and expiration dates, which are considered crucial for food safety. It is concluded that, although progress has been made, full compliance depends on more comprehensive technical support and regulatory policies that promote adequacy and consumer confidence.